Prevalence and antimicrobial resistance of Salmonella isolated from backyard pigs in Chiang Mai, Thailand - Chatchawan Anuchatkitcharoen (2020)
© 2020, Chiang Mai University - Faculty of Veterinary Medicine. All rights reserved. Salmonella is a zoonotic, global public health challenge. In Southeast Asia, backyard pigs are common and there is limited information about the prevalence of Salmonella and their risks to humans. This study was designed to determine prevalence and the antimicrobial resistance patterns of Salmonella in backyard pigs in Chiang Mai, Thailand. Ninety-three pooled fecal samples were collected from backyard pigs in three regions of Chiang Mai, Thailand during November 2016 – March 2017 for Salmonella isolation and antimicrobial susceptibility testing. The pooled prevalence of Salmonella in backyard pigs was 21.5%. Nine Salmonella serovars were identified including Salmonella I 4,5,12:i:-(31.0%), Salmonella Weltevreden (17.2%), Salmonella Rissen (13.8%), Salmonella Bovismorbificans (10.3%) and Salmonella Stanley (10.3%). The Salmonella isolates were commonly resistant to streptomycin followed by tetracycline, ampicillin and sulfamethoxazole/trimeth-oprim. No isolates were resistant to cefoxitin, nalidixic acid or imipenem. Sixteen different multi-resistant pattern were observed among isolates. The most frequent multi-resistant pattern was AMP-TET-SXT-S. Backyard pigs were harboring Salmonella and can serve as reservoirs transmitting infections to humans and other backyard animals. A variety of different serovars were isolated with a broad range of resistance profiles to different classes of antimicrobial agents. This provides evidence of the importance of educating owners and their families about the potential public health risk.